SERVANT LEADERSHIP PADA ORGANISASI VOLUNTEERING (STUDI MIX METHOD PADA ALUMNI LEADERSHIP DEVELOPMENT MODEL AIESEC UNDIP) - Brian Prabowo, Yoma Agustha; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2018)
Various types of leadership style exist and growth in the work environment of the organization. No exception, servant leadership. Nowadays, many organizations have tried to apply the concept of servant leadership in their operational practices, and AIESEC is one of them. This international leadership organization has a Leadership Development Model program that has the ultimate goal of inculcating the quality of leaders outlined in Leadership Development Qualities (LDQ). LDQ is what is felt to have in common with servant leadership. The purpose of this study is to find out how far the application of leadership that serves (servant leadership) in the life of the organization and daily life of AIESEC Undip’s alumnae and describe the values of servant leadership what is in them. In addition, this research is conducted to obtain information for the development of leadership programs in AIESEC.In this research, the sequential explanatory method is used. First, using the quantitative method, a modified servant leadership survey questionnaire was used to find out the alumni's assessment of the values of servant leadership in them. Then proceed with qualitative research conducted through interviews with the analysis of phenomenology approach, to dig deeper alumni experience related to the application of leadership values serving in their current organizational life. The reason for choosing the method is to explain in detail, because it is supported by answers to interviews that strengthen quantitative research, as well as design methods that are easy to explain and the exposure of results more easily reported.The results of this study show that leadership values that serve exist and have evolved in the alumni reflected in their experiences, as well as the AIESEC Leadership Development Model program can be said to be working well.